Puerto Rico's Caribbean development program: executive summary and graphs of projects promoted including the use of 936 funds (Puerto Rico. State Department San JuanPR, 1992)
Looks at the focus, impact, and commitment of the programme. Highlights production sharing; Section 936 of the UN Internal Revenue Code; new financing mechanisms; and technical assistance and collaboration. Presents statistics and several graphs of projects promoted.
Additional copy located in the Office of the Secretary-General